Training on the implementation of BOMBASTIK Game-Based Teaching Media (Board Game: Fun Learning Media to Increase Student Engagement) at SMAN 6 - Muljanto, Setia; Andini, Anggi Setia; Asri, Asri; Hasan, Debby; Agung, Agung; Farhi, Ahmad (Indonesian Journal of Community Empowerment (IJCE), 2025)
This community service activity aims to enhance student engagement in learning through the implementation of BOMBASTIK, a board game-based learning media, at SMAN 6. The program was carried out in three main stages, namely introduction, explanation, and practice of using the BOMBASTIK platform. The method applied emphasizes participatory training, enabling both teachers and students to experience interactive learning processes. The results show that the training successfully increased student motivation, collaboration, and active participation in the classroom. In addition, teachers gained new insights into innovative teaching strategies using game-based learning media. Overall, this activity demonstrates that board games can serve as effective learning tools to create a more dynamic and enjoyable educational environment.